INFLUENCE OF BURNOUT ON EMOTIONAL LABOUR AMONG SECONDARY SCHOOL TEACHERS IN THE MAKURDI METROPOLIS - Mngusuur Jam, Mngusuur; Saaondo, Patrick (African Journal of Social and Behavioural Sciences, 2024)
Due to the enormous job demands of a teacher, there is bound to be emotional labour associated with the work. If properly handled it would impact positively on the lives of students and lead to better teaching and learning. This study examines the influence of burnout on emotional labour among Secondary school teachers in the Makurdi metropolis. The cross- sectional research design was employed for the study. Maslach Burnout Inventory (MBI, 1983) and Emotional Labour Scales were used. Participants were selected through simple random sampling technique. The participants were made up of 237 (48.0%) males and 257(52.0%) females. The study has two main objectives, namely, to examine the influence of burnout on emotional labour among secondary school teachers in Makurdi metropolis and to explore gender differences in emotional labour among secondary school teachers in Makurdi metropolis. Multiple linear regression analysis and independent t-test were used to analyse data. Findings from the results revealed that overall burnout significantly and positively influenced emotional labour among secondary school teachers in Makurdi metropolis [F (3,490) =4652.728; P<.01; Finding also revealed that there were no significant gender differences in emotional labour among secondary school teachers in Makurdi metropolis t (df, 492) =.336; P>.05. The study concluded that burnout is a determinant of emotional labour. The higher the level of burnout by teachers, the higher the level of emotional labour. Gender differences were not a predictor of emotional labour among teachers. The study recommended, amongst others, that the Benue State Government, through the Ministry of Education, should design policies and programmes such as training on coping strategies and an increase in motivation that would add value to teachers’ welfare and productivity. More so, more teachers should be hired to complement the efforts of the existing ones to reduce heavy workloads, burnout and emotional labour. Training on coping strategies should be carried out to give teachers the resiliency training they needed to overcome psychological strain and emotional labour at work. This would increase efficiency and productivity among teachers in the state.